[PP.38.09] EFFECTS OF MILD DYNAMIC EXERCISE ON CIRCULATORY AND AUTONOMIC FUNCTION IN HEALTHY VOLUNTEERS. (September 2016) - Wolff, C.; Julu, P.O.; Collier, D.J.; Saxena, M.; Kapil, V.; Shah, M.; Eftychiou, S.; Mills, E.; Ansley, L.; Elliott, A.; Mukhtar, O.; Lobo, M.D.
Abstract : Objective: Valuable insights into BP regulation have arisen from the study of neurocirculatory responses to exercise. However most studies have focused exclusively on evaluation of responses to maximal/submaximal exercise with concomitant profound increase in muscle metabolic demand. We studied the effects of mild exercise in healthy volunteers to obviate the confounding effects of large metabolic changes. Design and method: 8 healthy volunteers undertook very mild dynamic exercise (< 3 METs) of 1 minute duration. Non-invasive arterial BP was monitored in all 8 subjects. In 5 subjects the arterial BP recording was used to derive haemodynamic variables (PulseCO®, LiDCO plc, London), including cardiac output (CO), mean arterial pressure (MAP), systemic vascular resistance (SVR) and heart rate. Autonomic nervous system investigation was undertaken in 7 subjects with high resolution monitoring of arterial pressure and electrocardiography to derive indices of sympathetic and parasympathetic tone (NeuroScope®, Medifit Instruments Ltd, London). Results: CO increased from an average resting value of 4.8 l min-1 to 6.2 l min-1 during exercise (a 30.4% increase, p = 0.003) and settled to 4.8 l min-1 afterwards. The reciprocal of SVR, conductance (100/SVR) was used to determine the role of the periphery on CO in positive terms (the other driver for the increase in CO being MAP change). The average increase in MAP and conductance was 4.4% (p = ns) and 23.8% (p = 0.01) respectively. Figure. No caption available. Cardiac sensitivity to baroreceptor function (CSB) fell from an average of 5.4 ± 1.2 SEM to 2.9 ± 1.2 SEM (p < 0.05) and cardiac vagal tone (CVT) fell from an average of 6.8 ± 1.3 SEM on a linear vagal scale to 4.1 ± 1.3 SEM, (p < 0.05). Following exercise rebound occurred with both to values above baseline. Conclusions: The main change driving the increase in CO was an increase in conductance rather than change in MAP. This is in contrast to dynamic cardiovascular exercise at higher workloads where MAP increases immediately and progressively with workload. Withdrawal of vagal tone at such mild exercise intensity is a new finding and is consistent with gradual heart rate increase as exercise intensity increases from the lowest levels.